Penerapan Analisis Altman Z-Score Sebagai Salah Satu Alat Untuk Mengetahui Potensi Kebangkrutan Perusahaan (Pada Perusahaan Telekomunikasi Yang Listing di BEI Periode Tahun 2009-2011) - TOPOWIJONO, .; HUSAINI, ACMAD; Brimantyo, Harril (Jurnal Administrasi Bisnis, 2013)
The objectives of this study is to predict bankruptcy by applying the Altman Z-Score method to telecommunication companies listed on the Indonesia Stock Exchange. The data used in this study are secondary data published on the Indonesia Stock Exchange in the year 2009-2011. This research uses quantitative research with descriptive analysis method. This research used company financial report to analyze. Based on application of Altman Z-Score method, the results of the four telecommunication companies shows that three of them indicated bankrupt for three consecutive years and one company indicated bankrupt for last two years. Keywords: Financial Report, Z-Score, Bankruptcy